Determining the antecedents of dynamic supply chain capabilities. Issue 4 (30th March 2020) - Aslam, Haris; Blome, Constantin; Roscoe, Samuel; Azhar, Tashfeen Mehmood
Abstract : Purpose: The purpose of this paper is to determine the antecedents of dynamic supply chain capabilities (DSCCs). The authors test entrepreneurial orientation (EO) and supply chain learning orientation (SCLO) as two antecedents of DSCCs. Design/methodology/approach: The paper uses structural equation modelling to test a hypothetical model. Data are gathered from a survey of 275 operations managers in Pakistan's turbulent manufacturing industry. Findings: The findings suggest that the weaker direct effects of EO, in comparison to the indirect effects, indicate that an SCLO mediates the relationship between EO and DSCCs. Research limitations/implications: It is widely accepted that firms do not compete with each other, instead, it is end-to-end supply chains that fight for market dominance. Many scholars use the dynamic capabilities view to understand supply chain level competition. However, the dynamic capabilities view is firm-centric in its examination of how companies transform internal resources to compete in the external environment. The theoretical contribution of this paper is a roadmap of how to build dynamic, supply-chain level and capabilities by determining the key antecedents. This paper explains that DSCCs emerge when buyers and suppliers share strategic orientations. Firms with an EO and the ability to learn with supply chain partners are well-positioned to develop DSCCs. This provides a new angle to theory testing by indicating that dynamic capabilities are enabled by an EO and an ability to learn with supply chain partners. Practical implications: Managers are given the building blocks of DSCCs, starting with fostering an entrepreneurially-oriented mindset in the company and then learning with supply chain partners. Entrepreneurially-oriented managers are encouraged to take risks and co-develop innovative ideas with suppliers during the supply chain learning process. Originality/value: This study is one of the earliest efforts to determine the strategic orientations that antecede the emergence of DSCCs.